EFFECT OF DIURNAL INTERMITTENT FASTING (DIF) ON ANTIOXIDANT AND PRO INFLAMMATORY MEDIATORS ACTIVITY IN MALE RAT MODEL OF TYPE 2 DIABETES MELLITUS - Ginting, Selamat; Siahaan, Jekson Martiar; Ginting, Chrismis Novalinda; Ok Yulizal, (African Journal of Infectious Diseases (AJID), 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, oxidative stress, and systemic inflammation. Diurnal intermittent fasting (DIF), a fasting pattern synchronized with circadian rhythms, has been proposed as a potential strategy to alleviate metabolic disturbances, but evidence from controlled animal studies remains limited. Materials and Methods: This experimental study employed a post-test-only control group design using thirty-six male Wistar rats. T2DM was induced by streptozotocin (65 mg/kg) and nicotinamide (230 mg/kg). Animals were randomized into four groups: diabetic control (G1), and three DIF-treated groups fasting two (G2), three (G3), and six (G4) days per week. Blood glucose was measured weekly. On day 28, serum levels of superoxide dismutase (SOD) and interleukin-6 (IL-6) were analyzed using enzyme-linked immunosorbent assay (ELISA). Results:DIF significantly reduced blood glucose levels in all intervention groups compared to the control (p < 0.05). The G4 group showed the highest SOD activity and the greatest IL-6 reduction (p < 0.05). However, there was no significant glucose difference between G3 and G4, suggesting a plateau in glycemic improvement. Conclusion: DIF improves glycemic control, enhances antioxidant defense through increased SOD activity, and reduces systemic inflammation via IL-6 suppression in a T2DM rat model. These findings support the potential of DIF as a complementary therapeutic approach for T2DM, although further research is needed to determine the optimal fasting regimen and its applicability in humans.